2016
DOI: 10.1007/s00894-016-2978-0
|View full text |Cite
|
Sign up to set email alerts
|

TD-DFT investigation of D–π–A organic dyes with thiophene moieties as π-spacers for use as sensitizers in DSSCs

Abstract: The geometrical, conformational, and electronic properties of a series of D-π-A metal-free dyes designed for use as sensitizers in DSSCs were studied using DFT and TD-DFT methods. A substituted triphenylamine moiety was used as the donor group and 2-cyanoacrylic acid as the acceptor group in these dyes. They also contained conjugated bridging π-linker groups containing two or more thiophene rings to enhance the intramolecular charge transfer. The B3LYP, M06-HF, ωB97XD and CAM-B3LYP functionals were utilized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…These dyes were connected using thiophene as π‐conjugated bridges and the photovoltaic properties confirm the suitable effects of the π‐conjugated bridge of the dye on the performance of the DSSC. Hasanein et al reported a series of metal‐free dyes with two or more thiophene moieties as π‐linkers, theirs results show the versatility of chemical structure modification as a tool for designing DSSC sensitizers with suitable efficiencies.…”
Section: Methodsmentioning
confidence: 99%
“…These dyes were connected using thiophene as π‐conjugated bridges and the photovoltaic properties confirm the suitable effects of the π‐conjugated bridge of the dye on the performance of the DSSC. Hasanein et al reported a series of metal‐free dyes with two or more thiophene moieties as π‐linkers, theirs results show the versatility of chemical structure modification as a tool for designing DSSC sensitizers with suitable efficiencies.…”
Section: Methodsmentioning
confidence: 99%
“…[51,[83][84][85] Moreover, DFT provides a range of functionals and amongst these, B3LYP has been found as a reliable functional for the determination of optical, electronic, as well as structural properties of smallto medium-sized organic molecules. [86][87][88][89] The results obtained, after benchmark tests based on experimental and theoretical data for various functionals, have shown that the results obtained with B3LYP are generally in good agreement with the corresponding experimental values. [90-94]-The optimized geometries were checked for any imaginary frequency in order to be sure enough that the optimized geometries represent the true minima.…”
Section: Computational Detailsmentioning
confidence: 97%
“…To avoid that a mistake is perpetuated, it should be noted that in the literature there are several reports using a wrong relation to determine V oc (see, for instance, References. [65][66][67][68][69][70][71][72][73][74]). In those cases, a confusion is made with the driving force for charge injection from the dye into the semiconductor, ∆G inj , which is calculated as the difference between the energy of the excited state of the dye (lowest unoccupied molecular orbital in DFT calculations), E dye* , and the TiO 2 conduction band edge, E CB [10,63,75]:…”
Section: Quantities Relevant To Device Performancementioning
confidence: 99%